Archaeological Imprints: We Follow Lines And Trace Them - Aldred, Oscar; Pálsson, Gísli (Journal of Contemporary Archaeology, 2018)
In this visual essay we discuss the role of creative practices in archaeology by examining the relationships between linotype printing and archaeological practices. We suggest that the two follow a shared trajectory: the way in which we interpret, follows and traces several kinds of interfaces. Our imprinted archaeology explores the implications of different acts of marking, cutting, and revealing the uncanny. Thus, we bring attention to the exchanges between us, as collaborators, but perhaps more significantly, the confluences between archaeology and creative practices by focusing on the similarities between the conceptual underpinnings of the archaeological process, such as excavation, though not exclusively, and the creative process of image-making, using linotype printing. We suggest that printing helps to bring attention to the idea that while archaeological excavation is an act of destruction, it is also a creative endeavour, full of possibilities as we follow and trace the lines that are created.